KEPALA SEKOLAH SEBAGAI MANAJER DALAM MENINGKATKAN MUTU PENDIDIKAN AGAMA ISLAM MULTIKULTURAL - Mastur, Mastur; Athar, Mohamad (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Managerial is an adjective related to leadership and management. In many literatures, the word managerial is often referred to as the origin of the word management which means to train horses or is literally interpreted as to handle which means to take care of, handle or control. Meanwhile, management is a noun which can mean management, leadership or administration. In principle, the definition of management has several characteristics as follows: (1) there is a goal to be achieved; (2) as a combination of science and art; (3) is a systematic, coordinated, cooperative and integrated process in utilizing its elements; (4) there are two people ormore who work together in an organization; (5) based on the division of work, duties and responsibilities; (6) includes multiple functions; (7) is a tool to achieve goals. The techniques used in this research on improving teacher quality are participatory observation techniques, in-depth interviews, and documentation. To obtain the data needed in this research, the researcher used several methods in the data collection process. The methods used to collect data in the field are the observation method, interview method and documentation method.